An Enantiospecific Polyene Cyclization Initiated by an Enantiomerically Pure Bromonium Ion. Issue 11 (26th July 2013) - Braddock, D. Christopher; Marklew, Jared S.; Foote, Kevin M.; White, Andrew J. P.
ABSTRACT Dimethylaluminum triflate‐mediated activation of tetrafluorobenzoates of enantiomerically pure bromohydrins results in enantiospecific polyene cyclizations. The initiation of cyclization by enantiomerically pure bromonium ions and subsequent propagation is not subject to catastrophic erosion of enantiomeric purity by any intramolecular or intermolecular bromonium ion‐to‐alkene transfer. Chirality 25:692–700, 2013. © 2013 Wiley Periodicals, Inc.